Decreased viability and proliferation of CHANG conjunctival epithelial cells after contact with ultraviolet light-irradiated pollen. (3rd July 2018) - Heidinger, Andrea; Rabensteiner, Dieter Franz; Rabensteiner, Jasmin; Kieslinger, Petra; Horwath-Winter, Jutta; Stabentheiner, Edith; Riedl, Regina; Wedrich, Andreas; Schmut, Otto
Abstract: Context: Contact with pollen is the major reason for the development of allergic symptoms on the ocular surface leading to a significant increase of allergic diseases worldwide. Environmental changes such as increased ultraviolet (UV) radiation and air pollution are discussed as contributory causes for this increase. Objective : We investigated the effect of UV light on the histamine content of pollen and examined if an irradiation of pollen affects the viability and proliferation of conjunctival cells. Materials and methods: Alder ( Alnus glutinosa ) and hazel ( Corylus avellana ) pollen were irradiated for different time periods with sunlight, UV-A or UV-B light and the histamine content was analysed and compared with non-irradiated pollen. Conjunctival epithelial cells (CHANG cells) were exposed to irradiated and non-irradiated pollen followed by an assessment of cell viability with the colorimetric MTS test and the impedance-based measurement of cell proliferation using the xCELLigence real-time analysis system. Results: UV light irradiation increased the histamine level of alder and hazel pollen in a dose-dependent manner. CHANG cells treated with irradiated pollen induced a statistically significant higher decrease of cell viability than treatment with non-irradiated pollen. Discussion and conclusions: Our results indicate that UV light is able to alter pollen thus making them more harmful for conjunctival cells.